(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
This paper contains detailed analysis of what implies organized crime, its definitions, and the scope of the criminal activities, the structure of the organization, its components, as well as the function of each member of the criminal organization. The research also includes information that was obtained from official source, namely, from authorities in charge of the fight against this type of crimes that impact not only on Paraguayan society, but also on all the other countries, this is why it is important for the States to sign conventions, agreements, treaties, whereby they commit to prosecute the fight against this problem, following the example of the United Nations Convention against Transnational Organized Crime (UNTOC), among others. Finally, this paper analyses the connection between the criminal organizations and drug trafficking and money laundry, as well as the classification, sanctions and other points to be considered when subsuming the illegal activities into the current legislation applicable to each particular case.